2009
DOI: 10.1007/s00421-009-1100-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preceding resistance exercise on metabolism during subsequent aerobic session

Abstract: The present study was undertaken to evaluate the acute effect of prior resistance training of varying intensities on energy expenditure and substrate utilization during subsequent aerobic exercise. Eleven males and 21 females completed three experimental trials consisting of (1) aerobic exercise only (C), (2) aerobic exercise preceded by a high-intensity resistance training (HI), and (3) aerobic exercise preceded by a low-intensity resistance training (LO). Resistance training produced an equal volume between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
3
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 26 publications
3
33
3
3
Order By: Relevance
“…This level of standardization was adopted because it appears to be the most commonly employed approach in our research field [3], [8], [28][32] and because more rigorous standardization is difficult to achieve both in out-clinic and research settings. Despite the standardization adopted, in some individuals a high intra-individual variability in Fat max and related variables was found, suggesting that a longer period of standardization (≥2 days prior to testing) might be needed to improve the reproducibility of those measures.…”
Section: Discussionmentioning
confidence: 99%
“…This level of standardization was adopted because it appears to be the most commonly employed approach in our research field [3], [8], [28][32] and because more rigorous standardization is difficult to achieve both in out-clinic and research settings. Despite the standardization adopted, in some individuals a high intra-individual variability in Fat max and related variables was found, suggesting that a longer period of standardization (≥2 days prior to testing) might be needed to improve the reproducibility of those measures.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in a study performed by Kang et al (2009), where were observed a significantly higher absolute VO 2 , in female subjects, between cycling in a cycle ergometer after ST exercise (3 sets of 8 reps of 6 exercises performed at 90% of the 8 RM and 3 sets of 12 reps of the 6 exercises performed at 60% of the 8 RM). Contrarily to Drummond et al (2005) and Kang et al (2009), on your unpublished data we not found significant differences during the AT exercise (cycling in a cycle ergometer), when this was followed or preceded of the ST exercises. A possible explanation of the differences between your data and Drummond et al (2005) resides on the device used for the AT exercise (cycle ergometer vs. treadmill, respectively).…”
Section: Introductionmentioning
confidence: 81%
“…It has been shown that the VO 2 kinetics is faster and the O 2 deficit is smaller for a given exercise when a previous bout of exercise is performed (Gerbino et al, 1996; Koppo and Bouckaert, 2000; Burnley et al, 2001; Scheuermann et al, 2001) involving the same muscle groups (Yoshida et al, 1995; Fukuba et al, 2002). The differences between Kang et al, (2009) and your unpublished data on the VO 2 during AT exercise, may have been with the variations on the intensities during the AT exercise , in your data, and in Kang et al, (2009), the same exercise was performed with same intensity in all period.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Other studies have shown that there were no differences between the aerobic and strength training and the intensity of exercise may have influence on the maintenance of the RMR, (Byrne & Wilmore, 2001;Lee, Sedlock, Flynn, & Kamimori, 2009) and on the type of the substrate recruited (Kang et al, 2009). …”
Section: At Groupmentioning
confidence: 97%